Effect of Internal Migration of Families on the Educational Achievement of their Children - Pandit, Sudesh; Adhikari, Ramesh (Asian Journal of Population Sciences, 2024)
This study explores the effects of the internal migration of parents with children on their children's educational achievement. PubMed and HINARI search engines perform advanced searches with specific keywords such as children, migration and educational achievement to extract relevant articles. During the review, 14 articles were identified by using the PRISMA flow diagram for the process of conducting a systematic review. The inclusion criteria specified internal migrant children with their parents and educational outcomes associated with them, with a publication date after within ten years. The search process yielded 8 articles that met the inclusion criteria for the final review. Positive effects are observed on educational achievement for children migrating with parents. Socioeconomic status, education level, and duration of migration influence the educational outcomes of children. Family and community support are important in coping with the difficulties of children's education. Policymakers and educators should address the challenges faced by internal migrant children.